Pemetaan Profil Kemampuan Penalaran Calon Guru Fisika di FKIP Universitas Mataram - Gunawan Gunawan (Department of Physics Education, Universitas Mataram, 2016)
Learning physics is not only produces a good learning outcomes, but requires the understanding, reasoning ability and conceptual understanding to solve the problems. Efforts that can be done to design a good learning is to mapping the ability of the learners. In this research, mapping of preservice physics teacherÃ¢â¬â¢s reasoning ability profile to know the description of the ability of spatial reasoning, logical reasoning and analytical reasoning. This is descriptive research. The population of this study includes all of students of physics education at Mataram University with the number of respondents as many as 125 students from the proportionally selected from each grade. The result of simple descriptive statistic test shows that students have higher spatial reasoning ability compared to logical and analytical reasoning ability as indicated by average score of reasoning ability test. Spatial reasoning skills of prospective teachersÃ¢â¬â¢ are also analyzed on the basis of their indicators. The highest scores is on the ability to complete the pattern and the lowest score is on the relation and logical consistency.